2018
DOI: 10.1186/s12913-018-2906-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a multicomponent pathway to address inpatient delirium on a neurosciences ward

Abstract: BackgroundDelirium is a frequent and detrimental complication of inpatient hospitalization. Multicomponent intervention in selected groups has been shown to prevent and treat delirium, though little data exists on the effect of intervention in neurological patients. We studied the efficacy of a multicomponent delirium care pathway implemented on a largely neurology and neurosurgery hospital ward among unselected patients.MethodsWe incorporated a multicomponent delirium care pathway into the workflow of a unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Six studies did not specify the number of patients undergoing craniotomy (i.e. requiring removal) [ 10 , 21 , 39 , 44 , 46 48 , 52 , 54 , 56 , 57 ]. Six studies did not report age, and seven studies did not report gender within the intracranial operated cohort [ 45 , 47 – 49 , 52 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Six studies did not specify the number of patients undergoing craniotomy (i.e. requiring removal) [ 10 , 21 , 39 , 44 , 46 48 , 52 , 54 , 56 , 57 ]. Six studies did not report age, and seven studies did not report gender within the intracranial operated cohort [ 45 , 47 – 49 , 52 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 4290 studies were screened on the title/abstract. Eventually, 47 studies were assessed full text, of which 27 excluded: delirium diagnosis not reproducible (n s (number of studies) = 9), [20][21][22][23][24][25][26][27][28] full text not found (n s = 3), [29][30][31] duplicate (n s = 3), [18,32] paediatric patients (n s = 1) [33], overlapping populations (n s = 3), [4,34,35] no delirium assessment (n s = 1), [36] no original data (n s = 2) [37,38] and an unclear number of patients undergoing intracranial surgery (n s = 5) [39][40][41][42][43]. Finally, 20 paper were included in the qualitative analysis and 18 papers in the quantitative analysis (n p (number of patients) = 5083).…”
Section: Systematic Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…We included 13 cohort studies with a control group and 11 case series without a control group. All 13 cohort studies [23][24][25][26][27][28][29][30][31][32][33][34][35], attained a score of 9 out of 11 on the JBI checklist for cohort studies (see S3 Table ), whilst 10 of the 11 case series [36][37][38][39][40][41][42][43][44][45][46], attained a full score of 10 on the JBI checklist for case series, with one study scoring 8 (S4 Table ). We observed that the majority of the primary studies (18 of 24 (75%)) included were published from year 2010 onwards.…”
Section: Characteristics and Quality Of Included Studiesmentioning
confidence: 99%
“…Often expression of POD cannot be explained by a pre-existing disorder and can impair ability to comply with medical care [4] , [5] . Diagnosis and treatment are complicated by a multitude of interactions between pre-operative vulnerabilities with intra-operative and post-operative precipitating factors [6] , [7] .…”
Section: Introductionmentioning
confidence: 99%